A Generation of Change : A Profile of America's Older Population - Siegel, Jacob S.; Hoover, Sally L.; Gendell, Murray (Book collections on Project MUSE., 1993)
As modern medicine extends the average life span and the baby boom generation begins to approach middle age, the number of older Americans is expected to more than double in the next century. But as national trends toward early retirement and low birthrate continue, an aging American population could face crises in meeting their financial and physical needs. A Generation of Change is an exceptional study of the demographic, social, and economic characteristics of the older population as it is today and as it will be in the coming years. Siegel employs census and survey data from 1950 through the mid-1980s to describe a population constantly shifting in its ethnic and gender composition, geographic distribution, marital and living arrangements, health, employment, and economic status. Surprisingly, there is tremendous disparity in the quality of life among the elderly. As the elderly progress from "young old" to the "aged old"--Those over 85 - sharp differences emerge as income and employment decrease and degrees of chronic illness increase. Although their average poverty rate is below that of the general population, there are dramatic levels of poverty among older women, who are far more likely than men to live alone or in institutions. Siegel analyzes the full range of characteristics for this heterogenous population and, through comparisons with other age groups as well as with the elderly of previous decades, portrays the crucial influence of social and economic conditions over the life course on the quality of later life. With our elderly population growing more numerous and long lived, accurate information about this changing group is increasingly essential.